A search for an articleamssymbemptydocument N =2 document inflaton potential. Issue 7 (29th April 2014) - Ceresole, A.; Dall'Agata, G.; Ferrara, S.; Trigiante, M.; Van Proeyen, A.
Abstract We consider <alternatives> <![CDATA[articleamssymbemptydocument N =2 document]]> <inline-graphic xlink:href="ark:/27927/pghms0k6m2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> supergravity theories that have the same spectrum as the R + R2 supergravity, as predicted from the off‐shell counting of degrees of freedom. These theories describe standard <alternatives> <![CDATA[articleamssymbemptydocument N =2 document]]> <inline-graphic xlink:href="ark:/27927/pghms0k6hh" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> supergravity coupled to one or two long massive vector multiplets. The central charge is not gauged in these models and they have a Minkowski vacuum with <alternatives> <![CDATA[articleamssymbemptydocument N =2 document]]> <inline-graphic xlink:href="ark:/27927/pghms0k6g0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> unbroken supersymmetry. The gauge symmetry, being non‐compact, is always broken. α‐deformed inflaton potentials are obtained, in the case of a single massive vector multiplet, with α = 1/3 and 2/3. The α = 1 potential (i.e. the Starobinsky potential) is also obtained, but only at the prize of having a single massive vector and a residual unbroken gauge symmetry. The inflaton corresponds to one of the Cartan fields of the non‐compact quaternionic‐Kähler cosets.